The Effect of Performance of LP3M Undana Employees on Quality Improvement and Implemenation of MBKM Regulations for the 2022/2023 Academic Year - FANGGITASIK, Chindy Hesty; NEOLAKA, Melkiesedek. N. B. C.; TODA, Hendrik (PT Keberlanjutan Strategis Indonesia, 2023)
Indonesian higher education institutions (PT) face many changes in the globalized era. To handle complex changes, PT education must be improved. University quality assurance is not only carried out externally. Permenristekdikti Number 62 of 2016 on the Higher Education Quality Assurance System requires universities to conduct the Internal Quality Assurance System autonomously (SPMI). The Undana Learning Development and Quality Assurance Institute (LP3M) implements quality assurance. The curriculum must also adapt to students' interests, needs, and expectations in revolution 4.0. The Central Government, through the Ministry of Education and Culture-Ristek, issued a policy of Free Learning and Independent Campus (MBKM). Human resources are an essential asset for the successful implementation of quality assurance and implementation of the MBKM policy. The research method used is a quantitative method to know and describe the effect of the performance of LP3M (X) Undana employees on internal quality improvement (Y1) and the implementation of the MBKM regulations for the 2022/2023 Academic Year (Y2).